The Sing and the Semiotic productivity at Umberto ECO - عباس, بشرى (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
In this research, we tried to identify the sign and the significances generated by it, which can change whenever the location of the sign changes, it was necessary first to explain the concept changes in every field in which we used the sign, and then we touched on the types of signs and how the significances change according to these types. So we talked about signs of persistence, metonymy and metaphor, and how these classifications led to the creation of the science of sign or semiology , and then we touched upon talking about the productivity of significance and the fields of this productivity, starting from the interpretation of the sign to the use of the sign in pragmatics.